Tissue engineering in hostile environments: the effects and control of inflammation in bone tissue engineering - Sidney, Laura E. (2013)
The potential effects of introducing bone regeneration strategies into environments of disease and damage are often overlooked, despite the fact that many of the signalling pathways in inflammation have effects on bone development and healing. Embryonic stem cells (ESCs) are increasingly being used to develop models of disease and have potential in osteogenic-cell based therapies. Osteogenic differentiation strategies for ESCs are well established, but the response of these cells to tissue damage and inflammation has not yet been investigated, particularly in comparison to primary osteoblasts. Here, proinflammatory cytokines were used as part of an in vitro model to mimic elements of skeletal disease, such as rheumatoid arthritis and non-union fractures. The response of osteogenically differentiated mouse embryonic stem cells (osteo-mESCs) to the proinflammatory cytokines interleukin 1-β (IL-1β), tumour necrosis factor-α (TNF-α) and interferon-γ (IFN-γ), was compared to that of primary mouse calvarial osteoblasts, already well-described in literature and used as a “benchmark” in this study. Although histology, immunocytochemistry and PCR showed similarities in osteogenic differentiation of the osteo-mESCs and the primary calvarial cells, over 21 days in culture, there were marked differences in the response to the proinflammatory cytokines. Viability of the osteo-mESCs was maintained in response to cytokines, whereas viability of primary cells was significantly reduced. There were marked increases in nitric oxide (NO) and prostaglandin E2 (PGE2) production in primary calvarial cells over the entire 21-day culture period, but this was not seen with osteo-mESCs until day 21. The study then went on to look at the effects of proinflammatory signalling on the in vitro bone formation of the two cell types. Significant differences in the effects of proinflammatory cytokines on bone nodule formation and matrix production were seen when comparing the osteo-mESCs and the calvarial cells. This study demonstrates that while osteo-mESCs share phenotypic characteristics with primary osteoblasts, there are some distinct differences in their biochemistry and response to cytokines. This is relevant to understanding differentiation of stem cells, developing in vitro models of disease, testing new drugs and developing cell therapies. An additional objective in this investigation was to look at tissue engineering strategies as a means of controlling inflammation in bone disease. The primary calvarial osteoblasts were utilised as an in vitro inflammation model, and used to study the effects of anti-inflammatory mediators. Anti-inflammatory-releasing porous scaffolds were manufactured from poly(lactic-co-glycolic acid) (PLGA) and poly(ethylene glycol) (PEG). The calvarial osteoblast inflammation model was used successfully to show successful release of diclofenac sodium from the PLGA/PEG scaffolds. This study demonstrates that there is much to consider in the development of regenerative strategies for bone disease, particularly the role that the effect and control of inflammation will play in bone healing.